PENGARUH NILAI TUKAR DAN SUKU BUNGA TERHADAP INDEKS FINANCE DI INDONESIA - B21108072, WILDA ADELIA (Jurnal Pembangunan dan Pemerataan, 2012)
Finance index is financial sector stock index which covers all banking and non banking financial institutions. Finance index has important role in fund transfer process in economy. This research aims to know the influence of USD currency in IDR and interest rate partially towards finance index. This causal research uses time series data that is analyzed by employing multiple linear regressions. The data is also tested by classical assumption test that consist of normality test, autocorrelation test, multicolinearrity test and heteroskedasticity test. This research shows that the regression equation passed classical assumption test. Simultaneously USD currency in IDR and interest rate influence finance index. Partially, only USD currency in IDR which has negative and significant influence towards finance index. There is medium correlation between independent and dependent variable. It is shown by correlation score of 0,548. The independent variables can explain the changes in finance index of 25,8%, while the rest of 74,2% changes in finance index is explained by other variable which are not observed in this research. Keywords: USD Currency in IDR, Interest Rate, and Finance Index